2017
DOI: 10.48048/wjst.2019.4017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychological Distress and Mental Health Problems among the Survivors in the Flash Floods and Landslide in Southern Thailand

Abstract: Significant evidence has shown that southern Thailand is prone to the highest risk of repeated flooding. However, psychological distress and mental health problems caused by the flash floods and landslides have been under-researched among Thai survivors. This cross-sectional study aimed to explore characteristics and factors associated with the prevalence of psychological distress, probable post traumatic stress disorder (PTSD), probable depression, suicide risk, and alcohol problems 4 to 6 months after the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Two studies assessed ASD, reporting prevalence estimates of 2.2% and 22.5%. Furthermore, two studies measured alcohol-related outcomes; Pollack et al 59 reported a 2% prevalence of storm-related alcohol dependence and Sonpaveerawong et al 66 reported a 17.2% prevalence of flood-related alcohol misuse.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies assessed ASD, reporting prevalence estimates of 2.2% and 22.5%. Furthermore, two studies measured alcohol-related outcomes; Pollack et al 59 reported a 2% prevalence of storm-related alcohol dependence and Sonpaveerawong et al 66 reported a 17.2% prevalence of flood-related alcohol misuse.…”
Section: Resultsmentioning
confidence: 99%
“…Five additional studies reported associations between climate change or climate-related disaster exposure severity and mental disorder outcomes, with largely mixed results. For example, Sonpaveerawong et al 66 found that experiencing flood-related injury was significantly associated with risk of suicide (OR 15.39, 95% CI 2.52 to 94.13) but not of PTSD, depression or alcohol abuse (p>0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Most prior studies on PTSD in Thailand have ex-plored its prevalence and the symptoms predictive factors among survivors of natural disasters. 6 However, Sonpaveerawong, et al, 7 reported that a critical protective factor from mental health problems related to natural disasters in Thailand, including PTSD symptoms, is the high social support that characterizes the Thai society.Together with cognitive behavioral therapy, the high social support has been supported by many studies to be effective in PTSD treatment among people residing in the insurgent areas of Southern Thailand. 8 So far, no previous study has attempted to elucidate a protective paradigm related to PTSD symptoms in the armed-conflict areas of Southern Thailand, which have markedly distinct contexts compared with the other parts of Thailand.…”
Section: Introductionmentioning
confidence: 99%